2009
DOI: 10.1161/strokeaha.108.531509
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT 2 Receptor Stimulation Causes Neuroprotection in a Conscious Rat Model of Stroke

Abstract: Background and Purpose-The angiotensin II type 2 receptor (AT 2 R) is implicated to be neuroprotective in stroke, although this premise has not been directly tested. Therefore, we have examined the neuroprotective effect of AT 2 R stimulation after intracerebroventricular administration of AT 2 R agonist CGP42112 in a conscious rat model of stroke. Methods-Spontaneously hypertensive rats were treated with either CGP42112 (0.1 to 10 ng/kg/min intracerebroventricularly) alone or in combination with the AT 2 R an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 42 publications
(57 reference statements)
10
101
1
Order By: Relevance
“…7 Candesartan has a similar effect, although it lowers blood pressure, 8 making it difficult to separate the effects of the drug from the beneficial effects of lowering blood pressure. Positive effects of AT 2 R activation have been shown previously by the authors of the current study, and in 2009 McCarthy et al 9 showed that CGP42112 reduces the damage caused by cerebral ischemia when administered 5 days before the ischemic insult. Importantly, as with the current study, the beneficial effects of AT 2 R activation were observed without the concomitant inhibition of the AT 1 R, suggesting that AT 2 R agonists can overcome the powerful detrimental effects of AT 1 R activation.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…7 Candesartan has a similar effect, although it lowers blood pressure, 8 making it difficult to separate the effects of the drug from the beneficial effects of lowering blood pressure. Positive effects of AT 2 R activation have been shown previously by the authors of the current study, and in 2009 McCarthy et al 9 showed that CGP42112 reduces the damage caused by cerebral ischemia when administered 5 days before the ischemic insult. Importantly, as with the current study, the beneficial effects of AT 2 R activation were observed without the concomitant inhibition of the AT 1 R, suggesting that AT 2 R agonists can overcome the powerful detrimental effects of AT 1 R activation.…”
supporting
confidence: 82%
“…One study using the filament occlusion model of ischemic stroke suggests that AT 2 R expression is increased after the induction of cerebral ischemia; these receptors were expressed only in neurons and appeared to promote neurite outgrowth. 7 Conversely, in the previous study from McCarthy et al, 9 it appears that AT 2 R expression is reduced after cerebral ischemia. The reason for this disparity in the results observed could be many fold and include the method of the induction of ischemia, the region of the brain studied, and the strain of rat used.…”
Section: Hypertensionmentioning
confidence: 80%
“…20 Clearly, there is an unmet need to develop a range of AT 2 R agonists to examine class effects of AT 2 R agonists directly in a number of cardiovascular diseases including heart failure 25 and stroke. 26 The majority of previous studies that have reported on novel Ang II peptides have examined binding profiles in a range of tissues with varying proportions of AT 1 R and AT 2 R, often with no functional correlate to assess functionality. In the present study, using homogenous ATRtransfected cell lines, we have shown that individual ␤-amino acid substitutions were well tolerated for AT 2 R binding but not for AT 1 R binding, suggesting the constraints on AT 1 R binding are more strict than AT 2 R. Consistent with these findings, alanine or glycine scans of Ang II caused only minor changes in AT 2 R binding affinity, whereas there was sometimes marked reduction in AT 1 R binding.…”
Section: Discussionmentioning
confidence: 99%
“…1 We reported that chronic treatment with AT 2 receptor (AT 2 R) agonist CGP42112 prevented brain ischemic injury in conscious spontaneously hypertensive rat. We showed evidence that AT 2 R stimulation preserved neuronal architecture and motor function, while suggesting that a local vasodilator component would likely contribute to the neuroprotection demonstrated.…”
Section: Responsementioning
confidence: 99%
“…11 An antioxidant action of AT 2 R has also been highlighted, with AT 2 R knockout mice exhibiting elevated levels of superoxide production after stroke, 12 a finding that is consistent with the reduction in superoxide production in infarcted tissue that we noted in response to CGP42112. 1 Thus, it is likely that there are multiple components to neuroprotection induced during AT 2 R stimulation, and the potential contribution of endothelial NO synthase and NO availability to this effect should not be ignored.…”
Section: Responsementioning
confidence: 99%